Probing Fistulae in the G.I. Tract (Res Medica, 2014)
Fistulae are commonly encountered in general surgery. A fistula is an abnormal connection between two epithelial surfaces (figure 1). It can connect two hollow viscera together, or can connect a hollow viscus to the skin. In this way they can either be visceral and internal, or cutaneous and external. The connection between the surfaces is usually lined with granulation tissue. A sinus is a granulating track from a source of infection to the surface. Sinuses can develop into fistulae if inadequately treated.